Theory and Practice of Therapeutic Massage - Beck, Mark F.; Photography by Chauvin, Yanik (Clifton Park, N.Y Thomson Delmar Learning, 2006)
This text is known for being comprehensive and readable Often used as the main text for programs that are about 500 hours, it covers all the key topics for individuals entering the profession with appropriate balance and depth. Individuals entering massage programs come from widely varied backgrounds; they are all ages, have held various positions, some health-related, some not. Beck is known for being the text that can bring all these student dynamics together under the umbrella of a very readable, approachable text. Students like the fact that the often daunting area of A & P and other clinically challenging learning objectives are made approachable through a unique body system approach to the content and a nice writing style. (Midwest).
Includes Index, Appendix, Colored Illustrations and Glossary
Keywords: Massage therapy -- Handbooks, manuals, etc